Breast cancer screening—opportunistic use of registry and linked screening data for local evaluation. Issue 3 (22nd September 2016) - Roder, David; Farshid, Gelareh; Gill, Grantley; Kollias, Jim; Koczwara, Bogda; Karapetis, Chris; Adams, Jacqui; Joshi, Rohit; Keefe, Dorothy; Powell, Kate; Fusco, Kellie; Eckert, Marion; et al.
Abstract: Rationale: Screening has been found to reduce breast cancer mortality at a population level in Australia, but these studies did not address local settings where numbers of deaths would generally have been too low for evaluation. Clinicians, administrators, and consumer groups are also interested in local service outcomes. We therefore use more common prognostic and treatment measures and survivals to gain evidence of screening effects among patients attending 4 local hospitals for treatment. Aims and objectives: To compare prognostic, treatment, and survival measures by screening history to determine whether expected screening effects are occurring. Methods: Employing routine clinical registry and linked screening data to investigate associations of screening history with these measures, using unadjusted and adjusted analyses. Results: Screened women had a 10‐year survival from breast cancer of 92%, compared with 78% for unscreened women; and 79% of screened surgical cases had breast conserving surgery compared with 64% in unscreened women. Unadjusted analyses indicated that recently screened cases had earlier tumor node metastasis stages, smaller diameters, less nodal involvement, better tumor differentiation, more oestrogen and progesterone receptor positive lesions, more hormone therapy, and less chemotherapy. Radiotherapy tended to be more common in screening participants. More frequent use of adjunctive radiotherapy applied when breast conserving surgery was used. Conclusions: Results confirm the screening effects expected from the scientific literature and demonstrate the value of opportunistic use of available registry and linked screening data for indicating to local health administrations, practitioners, and consumers whether local screening services are having the effects expected.